Investigating toxicity of urban road deposited sediments using Chinese hamster ovary cells and Chlorella Pyrenoidosa. (April 2020) - Guo, Qicong; Zhan, Yuting; Li, Yuqing; Hong, Nian; Guan, Yingjie; Zhang, Zhenxuan; Yang, Bo; Meng, Fanhua; Yang, Mengting; Liu, An
Abstract: Road deposited sediments (RDS) is the key carrier of pollutants in the urban road stormwater processes and hence has been seen as an important pollutant source of urban road stormwater. Although many research studies have focused on RDS and pollutants attached to RDS, the investigation on RDS toxicity is very limited. Toxicity test can permit an overall assessment on whether the RDS polluted stormwater can be safely reused. This paper used two living organisms, namely Chinese hamster ovary (CHO) cells, (mammalian cells to indicate human health related toxicity) and Chlorella Pyrenoidosa (algae to indicate ecological health related toxicity) to test RDS toxicity by using an innovative "equivalent toxicity area (ETA)" approach. The outcomes showed that mammalian cells are more sensitive than algae in terms of RDS toxicity. Pb, Cd and Cr primarily contributed to mammalian cell-based toxicity while Zn, Ni, Cu and TOC are primarily toxic to algae. It is also found that road site characteristics such as land uses exerted an important influence on RDS toxicity. Commercial areas tended to generate RDS with higher human health risk related toxicity while industrial areas had a potential to produce RDS with high ecological health risk related toxicity. The research outcomes also showed that solely focusing on pollutant themselves on RDS can not accurately indicate RDS pollution. An approach to considering both pollutant loads and toxicity is preferred. These results were expected to provide a useful insight to enhancing effectiveness of RDS polluted urban road stormwater management and ensuring their reuse safety. Graphical abstract: Image 1 Highlights: Road deposited sediments (RDS) toxicity was tested by two types of living organisms. Mammalian cells are more sensitive than algae in terms of RDS toxicity. Urban land uses exerted an important influence on RDS toxicity. Pb, Cd and Cr attached to RDS primarily contributed to mammalian cell-based toxicity. Zn, Ni, Cu and TOC attached to RDS are primarily toxic to algae.